Anna Jackson's I, Clodia: Catullus, women's voices, and feminist implications. (29th January 2018) - Lewis, Maxine
Abstract: Anna Jackson's I, Clodia substantially develops Catullus's literary reception. The collection complicates understandings of both Catullus's poetic paramour Lesbia and the historical Roman woman Clodia Metelli. Jackson makes Clodia a poet; she thus becomes not just a receiver of the classical tradition but a participant in it. Clodia responds to Catullus's poems with her own commentary on poetry, her own set of poetic devices, and a complex inter- and intratextuality. Moreover, Jackson makes Clodia a sensitive and literate reader of Catullus. While her Clodia takes a biographical approach to his poems, reading them as responses to their romance, she is also as attuned to his inter- and intratextual poetics as any modern Latin scholar. The poetic sequence has socio-cultural as well as aesthetic significance; by reimagining the much-maligned historical woman Clodia as an intelligent reader and a talented poet, I, Clodia serves as a feminist text. I, Clodia can be seen as part of the recent tradition of women writers reclaiming and rewriting women from the ancient world, complicating the notion that women writers now operate in a 'post-feminist' landscape.